The Composition of Undergrowth Vegetation in Forest Area with the Special Purpose of Gunung Bromo, Karangayar, Central Java, Indonesia - Abdul Ghaffar Amiruddin Zaki; Yus Andhini Bhekti Pertiwi; Malihatun Nufus; Amalia Tetrani Sakya (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Data on the biodiversity is essential to support the Forest Area with the Special Purpose (KHDTK) of Gunung Bromo as an educational forest and training center. This study aimed to obtain basic information on undergrowth vegetation composition under pine stands. Furthermore, the important value index (IVI), species diversity index (H'), species richness index (R), and evenness index (E) were determined. The data was systematically obtained by marking 35 plots of 2 m × 2 m. The distance between plots was 100 m. The results showed that the undergrowth vegetation consisted of 39 species from 26 families. The habitus of undergrowth vegetation was herb (15 species), shrub (14 species), liana (3 species), fern (6 species), and palm (1 species). Eragrostis tenerum was the dominant species with an IVI of 58.84%). Centrosema pubescens showed an IVI of 18.38%, while the other species showed less than 10%. Furthermore, H' was classified as moderate (2.35), R was classified as moderate (4.69), and E was classified as uneven (0.64). This condition indicated that the undergrowth species that grew in KHDTK of Gunung Bromo was limited and uneven. It was considered due to inhibiting factors such as allelopathy in pine leaf litter and low light intensity. Undergrowth species that grow in KHDTK of Gunung Bromo showed several potential utilizations, such as medicinal plants (30 species), ornamental plants (9 species), food sources (5 species), forage (4 species), culture and crafts (4 species), and conservation (3 species). Keywords: important value index, KHDTK of Gunung Bromo, species composition, species diversity, undergrowth vegetation